Before nature dies: from silent spring to our stolen future - Pulido Capurro, Víctor (2021)
The most outstanding aspects of the following three books are presented, the Silent Spring by Rachel Louise Carson, published in 1962; Before Nature Dies written by Jean Dorst, publishedin 1965, and Our Stolen Future written by Theo Colborn, Dianne Dumanoski and John Peterson Myers, published in 1996, which are based on scientific evidence, caused a great impact onthe world population, due to which they called attention to these issues; destruction of nature, the loss of species of animals and plants, the discriminatory use of pesticides such as DDTand chemicals that behave as disruptors that alter the endocrine system of organisms. They highlight the importance of social and ecological issues and recognize the need for a reflectionfrom bioethics and environmental education, which are part of the same speech that relates the scientific and the human. Also, how these books have somehow influenced a series of processes and mechanisms and agreements that have been made to protect the planet, habitats and species.